Survival Trends in Patients Under Age 65 Years With Mantle Cell Lymphoma, 1995–2016: A SEER-Based Analysis - Wu, Hongyu; Wang, Jianwei; Zhang, Xuanye; Yang, Hang; Wang, Yu; Sun, Peng; Cai, Qingqing; Xia, Yi; Liu, Panpan (Frontiers in Oncology, 2020)
Purpose: The treatment paradigm for mantle cell lymphoma (MCL), a B-cell malignancy, has shifted considerably during the past decades. This study aimed to evaluate time trends in overall survival (OS) and disease-specific mortality (DSM) of younger (age ≤65 years) patients with MCL from 1995 to 2016. Methods: We used the Surveillance, Epidemiology, and End Results database. Year of diagnosis was divided into three eras: the chemotherapy-alone era (1995–2000), intensified-immunochemotherapy era (2001–2012), and targeted-therapy era (2013–2016). We used the Kaplan–Meier method, log-rank test and subdistribution proportional hazard regression in the analysis. Results: A total 4892 patients were identified. Median OS increased from 67 months in the chemotherapy-alone era to 107 months in the intensified-immunochemotherapy era (P<0.001). The DSM rate decreased significantly from 1995 to 2016 (P<0.001); the adjusted hazard ratios of MCL-specific death were 0.589 (P<0.001) for the intensified-immunochemotherapy era and 0.459 (P<0.001) for targeted-therapy era, as compared with the chemotherapy-alone era. Patients with advanced-stage MCL had lower risk of death across the three eras (P<0.001). Conclusions: During 1995–2016, survival in younger patients with MCL increased significantly, especially those with advanced-stage disease, potentially reflecting the impact of advancement in treatment modalities on MCL outcome.